Novel xanthone antibacterials: Semi-synthesis, biological evaluation, and the action mechanisms. (1st April 2023) - Lu, Yan; Guan, Ting; Wang, Shaobing; Zhou, Cui; Wang, Meizhu; Wang, Xiaoyang; Zhang, Keyu; Han, Xiangan; Lin, Jinchao; Tang, Qun; Wang, Chunmei; Zhou, Wen
Graphical abstract: The SARs of twenty-one α-MG derivatives reveal that the contribution of the phenolic groups ranks as C3>C6>C1 in the antibacterial activity. 10a with one acetyl at C1 exhibits the high safety profiles, a strong ability in depolarizing membrane potentials to more leakage of bacterial proteins, presenting structural modifications at C1 suitable for developing α-MG-based antibacterial agents with little hemolysis and promising activity. Highlights: The SAR of α-mangostin derivatives against Gram positive bacteria is presented. The phenolic hydroxyl group of C3 α-mangostin for anti-Gram positive bacterial activity is necessary. Derivative 10a with the higher membrane selectivity, less hemolysis, and in vivo better antibacterial activity is discovered. The antibacterial mechanism of 10a may be involved in disturbed synthesis of proteins in the bioprocess of membrane potentials, permeability and integrity. Abstract: α-Mangostin (α-MG) has demonstrated to display potent activities against Gram-positive bacterial. However, the contribution of phenolic hydroxyl groups of α-MG to the antibacterial activity remains obscure, severely hampering selection of structure modification to develop more potential α-MG-based anti-bacterial derivatives. Herein, twenty-one α-MG derivatives are designed, synthesized and evaluated for the antibacterial activities. The structure activity relationships (SARs) reveal that the contribution of the phenolic groups ranks as C3 > C6 > C1, and the phenolic hydroxyl group at C3 is essential to the antibacterial activity. Of note, compared to the parent compound α-MG, 10a with one acetyl at C1 exhibits the higher safety profiles due to its higher selectivity and no hemolysis, and the more potent antibacterial efficacy in an animal skin abscess model. Our evidences further present that, in comparison with α-MG, 10a has a stronger ability in depolarizing membrane potentials and leads to more leakage of bacterial proteins, consistent with the results observed by transmission electron microscopy (TEM). Transcriptomics analysis demonstrates those observations possibly relate to disturbed synthesis of proteins participating in the biological process of membrane permeability and integrity. Collectively, our findings provide a valuable insight for developing α-MG-based antibacterial agents with little hemolysis and new action mechanism via structural modifications at C1.